PATTERNS OF FOREST LOSS PER TERRITORIAL CATEGORY IN THE AMAZON RAINFOREST: PERU (2001–2016) - Rubin de Celis, Ethel; Cruz-Burga, Zoila A.; La Torre-Cuadros, María de los Ángeles; Rosot, Nelson Carlos; Dalla Corte, Ana Paula; Araki, Hideo (Floresta, 2019)
The objective of the present study was to analyze the patterns of forest loss in the Peruvian Amazon between 2001 and 2016 according to 16 territorial categories and two types of land tenure (public and private) and administration (public and private). Through descriptive analysis and multivariate analysis using official forest loss data provided by the Peruvian government, a progressive increase in forest loss was detected over time, with the highest peaks in 2009, 2014, and 2016. The departments of San Martín, Loreto, and Ucayali presented the greatest loss. The three territorial categories with the greatest forest loss were the noncategorized areas (NCs), indigenous communities with land titles (ICTs), and rural lands (RLs). The NC category did not affect the general tendency of deforestation in Peru given that the forest loss dynamics in this category were similar to those of other territorial categories with assigned land rights.